PROSPECTS OF INNOVATIVE COMPUTER TECHNOLOGIES DEVELOPMENT IN HOSPITALITY INDUSTRY - A. Kalugina; Y. Makshanova; I. Rogova (Вестник университета)
Hospitality industry is one of the most prospective rapidly developing industries of the worls economy. Application of various innovative technologies in the sphere of hospitality is the key element in competitive management of a hotel enterprise. The article analyses modern innovation tendencies in the global market of hospitality management. The main trends of information technologies development and application are examined. Prospects of wide application of artificial intelligence and robotechnics in the future of hotspitality industry are considered.